Gly74Ser mutation in protein C causes thrombosis due to a defect in protein S-dependent anticoagulant function - Chen, Changming; Yang, Likui; Villoutreix, Bruno O.; Wang, Xuefeng; Ding, Qiulan; Rezaie, Alireza R. (Thrombosis and Haemostasis, 2017)
Protein C is a vitamin K–dependent serine protease zymogen in plasma which upon activation by thrombin in complex with thrombomodulin (TM) down-regulates the clotting cascade by a feedback loop inhibition mechanism. Activated protein C (APC) exerts its anticoagulant function through protein S-dependent degradation of factors Va and VIIIa. We recently identified a venous thrombosis patient whose plasma level of protein C antigen is normal, but its anticoagulant activity is only 34% of the normal level. Genetic analysis revealed that the proband and her younger brother carry a novel heterozygous mutation c.346G>A, p.Gly74Ser (G74S) in PROC. Thrombin generation assay indicated that the TM-dependent anticoagulant activity of the proband’s plasma has been significantly impaired. We expressed protein C-G74S in mammalian cells and characterised its properties in established coagulation assays. We demonstrate that the protein C variant can be normally activated by the thrombin-TM complex and the resulting APC mutant also exhibits normal amidolytic and proteolytic activities toward both FVa and FVIIIa. However, it was discovered the protein S-dependent catalytic activity of APC variant toward both procoagulant cofactors has been significantly impaired. Protein S concentration-dependence of FVa degradation revealed that the capacity of APC variant to interact with the cofactor has been markedly impaired. The same results were obtained for inactivation of FVa-Leiden suggesting that the protein S-dependent activity of APC variant toward cleavage of Arg-306 site has been adversely affected. These results provide insight into the mechanism through which G74S substitution in APC causes thrombosis in the proband carrying this mutation.
Keywords: Protein C; protein S; factor Va; factor VIIIa; thrombosis